Digital-First Learning and Assessment Systems for the 21st Century - Langenfeld, Thomas; Burstein, Jill; von Davier, Alina A. (Frontiers in Education, 2022)
In the past few years, our lives have changed due to the COVID-19 pandemic; many of these changes resulted in pivoting our activities to a virtual environment, forcing many of us out of traditional face-to-face activities into digital environments. Digital-first learning and assessment systems (LAS) are delivered online, anytime, and anywhere at scale, contributing to greater access and more equitable educational opportunities. These systems focus on the learner or test-taker experience while adhering to the psychometric, pedagogical, and validity standards for high-stakes learning and assessment systems. Digital-first LAS leverage human-in-the-loop artificial intelligence to enable personalized experience, feedback, and adaptation; automated content generation; and automated scoring of text, speech, and video. Digital-first LAS are a product of an ecosystem of integrated theoretical learning and assessment frameworks that align theory and application of design and measurement practices with technology and data management, while being end-to-end digital. To illustrate, we present two examples—a digital-first learning tool with an embedded assessment, the Holistic Educational Resources and Assessment (HERA) Science, and a digital-first assessment, the Duolingo English Test.